MAGI DAN AGAMA DALAM PANDANGAN JAMES GEORGE FRAZER - Putu Sanjaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
James George Frazer is a religious theorist. Born January 1, 1854 in Glasgow, Scotlandfrom a Protestant family, he was also one of theorists in a book called Seven the theory ofreligion. The reading of a number of books finds James George Frazer's view of the origin of areligion that, humans have religious behavior, in the form of skills, the ability to manipulate andcondition nature through a special initiation called Magi. Magic activity is a primordial humanreligious activity in the past. How does magi become a religion? Is a problem to be sought inthis paper. This paper uses a literature approach, which is done by reading a number of librariesrelating to religious studies, then, the reading of a number of libraries is presented back into thispaper. In conclusion, religion in the view of James George Frazer stems from the activity ofmagic that is practiced to fulfill the human religious desire.